VERTICAL GARDEN : PENGHIJAUAN UNTUK MENDUKUNG SMART LIVING DI KOTA YOGYAKARTA - Aviana Vety Jayanti; Eko Priyo Purnomo; Aulia Nurkasiwi (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: Increasingly dynamic city development without being accompanied by the provision of vacant land for reforesting has a negative impact on the environment. Increasing air quality and noise levels make a city have to prepare solutions to solve problems that have an impact on the environment of human life. The concept of vertical garden emerged as an alternative greening that can be applied in cities with a level of availability of narrow vacant land such as the city of Yogyakarta. The impact of applying this concept can overcome problems such as decreased air quality due to pollution. This study uses qualitative methods to describe how the effect of applying vertical gardens as an alternative to greening in supporting smart environments.Keywords: Smart Environment, Vertical Garden, Environment;